2001
DOI: 10.1016/s0378-1097(01)00213-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of epithelial cell apoptosis by Porphyromonas gingivalis

Abstract: Porphyromonas gingivalis is periodontal pathogen that is capable of invading gingival epithelial cells (GECs). Apoptotic responses of primary cultures of GECs to P. gingivalis were investigated with a DNA fragmentation ELISA assay. P. gingivalis induced a transient increase in GEC DNA fragmentation; however, after prolonged incubation GECs did not undergo apoptosis. Furthermore, P. gingivalis blocked apoptosis in GECs following stimulation with camptothecin. Immunoblotting of GECs with Bcl-2 or Bax antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(124 citation statements)
references
References 15 publications
(32 reference statements)
9
113
2
Order By: Relevance
“…Hence, reduced protease expression will contribute to the long-term survival of the host cells. In support of this concept, epithelial cells infected with P. gingivalis do not undergo apoptosis [50] and can survive for up to eight days after infection [6]. Thus, intracellular P. gingivalis appear to be adapted for long-term survival and coexistence with the host, and may not be overtly pathogenic.…”
Section: Insights Into the Intracellular Lifestyle Of P Gingivalismentioning
confidence: 99%
“…Hence, reduced protease expression will contribute to the long-term survival of the host cells. In support of this concept, epithelial cells infected with P. gingivalis do not undergo apoptosis [50] and can survive for up to eight days after infection [6]. Thus, intracellular P. gingivalis appear to be adapted for long-term survival and coexistence with the host, and may not be overtly pathogenic.…”
Section: Insights Into the Intracellular Lifestyle Of P Gingivalismentioning
confidence: 99%
“…These observations support the notion that P. gingivalis is present in small numbers when compared with the total microbiota of the periodontal pockets (Kumar et al, 2006) and, as it remains in the intracellular environment, can multiply and spread to neighboring cells (Tribble and Lamont, 2010), obtaining not only a privileged position to modulate the immune response, causing a 'dysbiosis' between the host and the subgingival microbiota (Darveu et al, 2012), but also a location that allows P. gingivalis to escape from the host eliminating mechanisms and from mechanical periodontal treatment, perpetuating the chronicity of the periodontitis. Furthermore, the existence of overloaded cells supports the ability of the host cells to withstand an extensive P. gingivalis colonization without losing viability, due to the induction of antiapoptotic mechanisms by P. gingivalis as a survival strategy (Nakhjiri et al, 2001). We were unable to detect A. actinomycetemcomitans in our subgingival plaque samples.…”
Section: Discussionmentioning
confidence: 69%
“…Caspase-dependent P. gingivalis-induced apoptosis: Because of the close proximity between oral pathogens and host cells in the gingiva, the interplay of P. gingivalis and the various cell types present in the gingival crevice has been under intense scrutiny. It is becoming increasingly clear that host cell responses to pathogenic bacteria can involve either elevated apoptosis or suppression of cell death (144). The body of evidence reveals that P. gingivalis-induced apoptosis is cell type-specific.…”
Section: Apoptosis Can Occur With and Without Caspase Involvementmentioning
confidence: 99%
“…In addition, it has been demonstrated that P. gingivalis LPS can prevent apoptosis of neutrophils derived from a human promyelocytic cell line, which may prolong an acute inflammatory response resulting in an increased potential for tissue destruction (140). Experimental results of Nakhjiri, et al, suggested that the first response to P. gingivalis infection in primary gingival epithelial cells was apoptosis; however, over time P. gingivalis initiated anti-apoptotic signaling via increased levels of Bcl-2 and decreased levels of Bax that canceled the cells' death response and was even able to promote cell survival in the presence of the apoptotic inducer camptothecin (144). Furthermore, inhibition of the PI3-K/Akt pathway abolished the P. gingivalis-induced protection from apoptosis (230).…”
Section: P Gingivalis-induced Resistance To Apoptosismentioning
confidence: 99%
See 1 more Smart Citation